Brand image, trust dan quality of information pada consumer purchase decisions - Nikmah, Masfi’atun (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to reveal the effect of brand image, trust, and quality of information either partially or simultaneously on consumer purchasing decisions. This research is quantitative research using a questionnaire as an instrument. The respondents of this research were the users of the Shopee online application in the West Surabaya area, with a total of 80 respondents using non-probability sampling and incidental sampling. Meanwhile, the analysis technique used is multiple linear regression. The results show that brand image, trustworthiness, and information quality have a joint effect on purchasing decisions. In this study also found that, partially brand image has no effect on purchasing decisions. Trust and the quality of information affect purchasing decisions. The amount of brand image analysis, trustworthiness and quality of information on purchasing decisions (R Square) is 0.879 or 87.9%..